Evaluation of HCV treatment in people who actively inject drugs. (July 2016) - Alimohammadi, Arshia; Hakobyan, Syune; Raycraft, Tyler; Vafadary, Sahand; Conway, Brian
Aim: HCV treatment in people who actively inject drugs (PWID) (active PWID) is sometimes withheld. We propose that active PWID can be treated for HCV in the right setting.Methods: HCV-infected active PWID were evaluated at a multidisciplinary clinic in an observational study. The primary end point was a sustained virologic response following HCV therapy.Results: We included 40 active PWID, of which 63% used heroin, 70% used cocaine and 37% received all-oral regimens. With a mean follow-up of 570 days, 78% subjects achieved sustained virologic response (93% on all-oral regimens; p < 0.05), with no recurrent viremia.Conclusion: Active PWID can be effectively treated for HCV, especially with all-oral regimens and rates of recurrent viremia can be reduced in a multidisciplinary healthcare setting.